Immunoactive polysaccharides produced by heterotrophic mutant of green microalga Parachlorella kessleri HY1 (Chlorellaceae) - Sushytskyi, Leonid; Lukáč, Pavol; Synytsya, Andriy; Bleha, Roman; Rajsiglová, Lenka; Capek, Peter; Pohl, Radek; Vannucci, Luca; Čopíková, Jana; Kaštánek, Petr (Carbohydrate polymers, 2020)
Hot water extract from biomass of heterotrophic mutant green alga Parachlorella kessleri HY1 (Chlorellaceae) was deproteinised, and three polysaccharidic fractions were obtained by preparative chromatography. The low-molecular fraction (1.5 × 104g mol-1) was defined mainly as branched O-2-β-xylo-(1→3)-β-galactofuranan where xylose is partially methylated at O-4. Two high-molecular fractions (3.05 × 105 and 9.84 × 104g mol-1) were complex polysaccharides containing α-l-rhamnan and xylogalactofuranan parts in different ratios. The polysaccharides were well soluble in hot water and, upon cooling, tended to self-segregate. Immunomodulatory activities of the obtained fractions were preliminary tested using ELISA, FACS and ImmunoSpot kits. The polysaccharides increased the TNF-α production in melanoma bearing mice with much higher intensity than in healthy mice. This was in agreement with the FACS results on T and B cells indicating their possibly secondary activation by innate immunity cells.
Keywords: Gene Expression Regulation; molekulová hmotnost; Immunologic Factors; sacharidové sekvence; primární buněčná kultura; Lipopolysaccharides; Interferon-gamma; Tumor Necrosis Factor-alpha; rostlinné extrakty; Interleukin-2; Molecular Weight; lipopolysacharidy; Skin Neoplasms; Antigens, CD; voda; Chlorophyta; CD antigeny; Methylation; metylace; B-lymfocyty; interferon gama; interleukin-4; rozpustnost; polysacharidy; T-lymfocyty; Interleukin-4; Melanoma; Animals; Plant Extracts; interleukin-2; xylosa; zvířata; regulace genové exprese; myši inbrední C57BL; myši; Carbohydrate Sequence; TNF-alfa; Mice, Inbred C57BL; B-Lymphocytes; nádory kůže; T-Lymphocytes; Polysaccharides; imunologické faktory; Mice; Xylose; melanom; Primary Cell Culture; Water; Solubility